Results of the prospective multicenter SoLKiD cohort study indicate bio-psycho-social outcome risks to kidney donors 12 months after donation. - Suwelack, Barbara; Berger, Klaus; Wolters, Heiner; Gerss, Joachim W. O.; Bormann, Eike; Woermann, Viktorya; Burgmer, Markus (Kidney International, 2022)
The outcome after living kidney donation was assumed to be comparable to that of the general population. However, recent register studies reveal negative changes in kidney function, quality of life and fatigue. Avoiding methodological issues of previous studies, the Safety of the Living Kidney Donor (SoLKiD) cohort study analyzed the outcome of donors in a multicenter and interdisciplinary fashion. Donor data were collected pre-donation and two-, six- and 12-months post-donation in 20 German transplantation centers. Primary parameters were kidney function, quality of life, and fatigue. Secondary endpoints were blood pressure, hemoglobin, hemoglobin A1c, body mass index, depression and somatization. Parameters were analyzed with non-parametric statistical tests and a mixed model regression for changes in time, their clinical relevance and interaction encompassing 336 donors with mean age of 52 years. Most of the physical secondary parameters, depression, and quality of life showed little or no changes and regained their pre-donation level. Kidney function decreased significantly with a 37% loss of glomerular filtration rate and an increase of donors with chronic kidney disease stage 3 from 1.5% pre-donation to about 50%. Donors consistently showed increased fatigue and somatization. Mental fatigue increased from 10.6% to 28.1%. The main influencing factors for decreased kidney function and increased fatigue were their respective pre-donation levels, and donor age for kidney function and subject stress level in fatigue. Thus, our study showed that a significant number of donors developed clinically relevant changes in physical and mental health and emphasizes the urgent need to inform potential donors about these risks.
EVALuna2:488808